2005
DOI: 10.1007/s12055-005-0001-y
|View full text |Cite
|
Sign up to set email alerts
|

Coronary endarterectomy for diffuse extensive coronary artery disease

Abstract: Introduction: Atherosclerotic coronary artery disease is in an increasing trend in India. With the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In our study, the number ofa positive inotropic requirement was 68 (69.3%) and IABP support was required in 23 (23.4%) patients. Padhy et al [11] statedthese rates as 64.2% and 16.6%, respectively.…”
Section: Hap3#2au`$ A#)a$ __ 4'22$ E?@a2#and$ A$ A#)a$ ___ =?@Uhfp'(#$ mentioning
confidence: 96%
“…In our study, the number ofa positive inotropic requirement was 68 (69.3%) and IABP support was required in 23 (23.4%) patients. Padhy et al [11] statedthese rates as 64.2% and 16.6%, respectively.…”
Section: Hap3#2au`$ A#)a$ __ 4'22$ E?@a2#and$ A$ A#)a$ ___ =?@Uhfp'(#$ mentioning
confidence: 96%
“…9, 10 WD Jhonson and DA Cooley who performed a large series of coronary end arterectomy revealed that there is an increase in surgical risk and good long term effect in selected group of patient. 11 We could get a small number of end artrectomy samples after surgical procedure from Department of Cardiothoracic Surgery as it is a rare procedure and potential cause for surgical complications.…”
Section: Discussionmentioning
confidence: 99%